2015
DOI: 10.3390/ijerph120100910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Horizontal Acceleration on Human Visual Acuity and Stereopsis

Abstract: The effect of horizontal acceleration on human visual acuity and stereopsis is demonstrated in this study. Twenty participants (mean age 22.6 years) were enrolled in the experiment. Acceleration from two different directions was performed at the Taiwan High-Speed Rail Laboratory. Gx and Gy (< and >0.1 g) were produced on an accelerating platform where the subjects stood. The visual acuity and stereopsis of the right eye were measured before and during the acceleration. Acceleration <0.1 g in the X- or Y-axis d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
1
4
0
Order By: Relevance
“…From this experiment we can draw the following three conclusions which are applicable to both the TV and VR scenarios. Firstly, users performed better at the static visual acuity test than at the dynamic test which is in line with past studies [8], [31]. Secondly, dynamic acuity correlated with perception of impairment.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…From this experiment we can draw the following three conclusions which are applicable to both the TV and VR scenarios. Firstly, users performed better at the static visual acuity test than at the dynamic test which is in line with past studies [8], [31]. Secondly, dynamic acuity correlated with perception of impairment.…”
Section: Discussionsupporting
confidence: 90%
“…From the literature we learn that visual acuity declines when horizontal movement of the head increases due to an imperfect pursuit of eye movements, resulting in a continued image motion on the retina [8]- [10]. For television (TV) and VR, we expected to find a similar pattern.…”
Section: Introductionmentioning
confidence: 91%
“…To evaluate the stability of sharpness, the measurements were repeated 5 minutes later. Also, to check the repeatability and accuracy of VA, the measurements were compared to measurements recorded with a portable Rosenbaum pocket vision screener and E chart [19,20].…”
Section: Va=01+related Row Logarithm Value -(0034* Numbers Of Read Le...mentioning
confidence: 99%
“…In addition, within the horizontal vibration range of 0.2 to 0.8 Hz, motion sickness is closely related to the peak velocity of vibration [9][10] . In 2015, Horng C T et al demonstrated the effect of horizontal acceleration on human vision and stereo vision through experiments 11 . The subjective evaluation method is often used to evaluate the level of dizziness among passengers, including questionnaire surveys such as susceptibility to dizziness, dizziness assessment questionnaire, pain level scale, and symptom diagnosis method 12 .…”
Section: Introductionmentioning
confidence: 99%